Ethnic Minority Muslim Social Pedagogy (Counter-radicalism of Chinese Muslims through Islamic Education) (Program Studi Pendidikan Agama Islam, 2020)
This paper aims to discuss the efforts of Chinese Muslims in practicing Islamic education in their minority communities. By using a social pedagogical approach model in Islamic education, Chinese Muslims make social and cultural issues a starting point for religious understanding. As a minority social entity, Chinese Muslims who are members of PITI (Indonesian Chinese Muslim Association), also try to transmit their Islamic knowledge not co-opted by radical Islamic religious doctrines. By using qualitative-phenomenological research methods, this study has succeeded in finding that this minority Muslim community's social pedagogy realizes by involving three elements simultaneously: teaching, acculturation, and social action in Islamic education. Through this strategy, Chinese Muslims try to become devout Muslims without reducing their cultural reality as a Chinese. In another position, the Chinese Muslim social pedagogy approach seeks to carry out the de-radicalization movement using socio-cultural instruments through academic activities in Islamic education.